2018
DOI: 10.1016/j.str.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamic Funnel Drives Bacterial Lipopolysaccharide Transfer in the TLR4 Pathway

Abstract: The Gram-negative bacterial outer membrane contains lipopolysaccharide, which potently stimulates the mammalian innate immune response. This involves a relay of specialized complexes culminating in transfer of lipopolysaccharide from CD14 to Toll-like receptor 4 (TLR4) and its co-receptor MD-2 on the cell surface, leading to activation of downstream inflammatory responses. In this study we develop computational models to trace the TLR4 cascade in near-atomic detail. We demonstrate through rigorous thermodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 78 publications
4
42
0
Order By: Relevance
“…[60] developed a computational model to study the thermodynamics and affinity of the receptor complex in the process of LPS transfer to TLR4 and suggested that the lipid affinity increases along the TLR4 signaling cascade. The affinity for lipid A binding to CD14 (136 ± 13 kJ mol −1 ) is less than the affinity for MD2 (156 ± 11 kJ mol −1 ) and lipid A binding to the MD2/TLR4 complex (~400 kJ mol −1 ) is the most thermodynamically favored event [61]. Furthermore, Phe126 residue in MD2 is important for the transfer of LPS from CD14 to the TLR4-MD2 complex which acts as a hydrophobic switch to mediate the signaling at the TLR4 complex dimerization interface [60,61].…”
Section: Lps Recognition By Tlr4mentioning
confidence: 95%
See 1 more Smart Citation
“…[60] developed a computational model to study the thermodynamics and affinity of the receptor complex in the process of LPS transfer to TLR4 and suggested that the lipid affinity increases along the TLR4 signaling cascade. The affinity for lipid A binding to CD14 (136 ± 13 kJ mol −1 ) is less than the affinity for MD2 (156 ± 11 kJ mol −1 ) and lipid A binding to the MD2/TLR4 complex (~400 kJ mol −1 ) is the most thermodynamically favored event [61]. Furthermore, Phe126 residue in MD2 is important for the transfer of LPS from CD14 to the TLR4-MD2 complex which acts as a hydrophobic switch to mediate the signaling at the TLR4 complex dimerization interface [60,61].…”
Section: Lps Recognition By Tlr4mentioning
confidence: 95%
“…The affinity for lipid A binding to CD14 (136 ± 13 kJ mol −1 ) is less than the affinity for MD2 (156 ± 11 kJ mol −1 ) and lipid A binding to the MD2/TLR4 complex (~400 kJ mol −1 ) is the most thermodynamically favored event [61]. Furthermore, Phe126 residue in MD2 is important for the transfer of LPS from CD14 to the TLR4-MD2 complex which acts as a hydrophobic switch to mediate the signaling at the TLR4 complex dimerization interface [60,61]. demonstrated that LPS binding leads to the dimerization of the TLR4/MD2-LPS complex, and LPS interacts with the hydrophobic pocket in MD-2 where five of six lipid chains are buried deep inside the pocket and one is exposed to the surface which interacts with a second TLR4 molecule.…”
Section: Lps Recognition By Tlr4mentioning
confidence: 95%
“…15. This involved switching the GL0 and GL5 beads in our original E. coli LPS CG model and shortening the lengths of the carbon lipid tails (30). The initial CG model for S. aureus LTA was initially constructed based on an atomic model kindly provided by Dr. T. J. Piggot.…”
Section: Thrombin Fragments Aggregate Bacteria Molecular Dynamics Simmentioning
confidence: 99%
“…to Toll-like receptor 4 (TLR4) and its co-receptor MD-2 on the cell surface, leading to activation of downstream inflammatory responses (11). In order to probe whether the presentation and hence, activity of LPS was altered by the interaction with S protein, we decided to study the pro-inflammatory effects of S with or without LPS using THP1-XBlue-CD14 cells.…”
Section: Effects Of Sars-cov-2 S Protein On Lps-induced Responses Inmentioning
confidence: 99%